2014
DOI: 10.1175/mwr-d-13-00055.1
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Synoptic to Quasi-Biweekly Disturbances in Generating the Summer 2003 Heavy Rainfall in East China

Abstract: During the mei-yu season of the summer of 2003, the Yangtze and Huai River basin (YHRB) encountered anomalously heavy rainfall, and the northern YHRB (nYHRB) suffered a severe flood because of five continuous extreme rainfall events. A spectral analysis of daily rainfall data over YHRB reveals two dominant frequency modes: one peak on day 14 and the other on day 4 (i.e., the quasi-biweekly and synoptic-scale mode, respectively). Results indicate that the two scales of disturbances contributed southwesterly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…For instance, both Lu et al (2014) and Zhu et al (2003) revealed that floods in the Yangtze River Basin during 1998 were in tandem with the active phase of 30-60-day BSISO. Liu et al (2014) emphasized the great contribution of the quasi-biweekly agent to heavy rainfall in the Yangtze-Huai River Valley during 2003. Studies based on specific cases can't fully address influences of the BSISO on precipitation extremes in China.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, both Lu et al (2014) and Zhu et al (2003) revealed that floods in the Yangtze River Basin during 1998 were in tandem with the active phase of 30-60-day BSISO. Liu et al (2014) emphasized the great contribution of the quasi-biweekly agent to heavy rainfall in the Yangtze-Huai River Valley during 2003. Studies based on specific cases can't fully address influences of the BSISO on precipitation extremes in China.…”
Section: Introductionmentioning
confidence: 99%
“…Previous flooding case studies found that the unusually persistent episodes of wet condition in southern China were related to convective phases of boreal summer intraseasonal oscillation (BSISO) (Yang and Li, ; Zhu et al , ; Mao and Wu, ; Gao et al , ; Liu et al , ; Li et al , ). The BSISO has been identified as the dominant source of short‐term climate variability and extremes in Asia (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In other ways, it was documented that the QBWO could influence the active/broken cycles of Indian summer monsoon (Krishnamurti and Ardanuy 1980;Yasunari 1981;Goswami et al 2003) and South China Sea (SCS) summer monsoon (Chen et al 2000;Chan et al 2002;Mao and Chan 2005;Zhou and Miller 2005). Some studies also indicated that the QBWO was closely related to the rainfall in the Yangtze and Huai River basin of China in boreal summer (Yang et al 2010;Liu et al 2014). Besides, the QBWO could impact the track of the tropical cyclone.…”
Section: Introductionmentioning
confidence: 99%